2012
DOI: 10.1155/2012/504367
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis of the Effect of Plaques in the Left Coronary Artery

Abstract: This study was to investigate the hemodynamic effect of simulated plaques in left coronary artery models, which were generated from a sample patient's data. Plaques were simulated and placed at the left main stem and the left anterior descending (LAD) to produce at least 60% coronary stenosis. Computational fluid dynamics analysis was performed to simulate realistic physiological conditions that reflect the in vivo cardiac hemodynamics, and comparison of wall shear stress (WSS) between Newtonian and non-Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…These low-flow regions are associated with low WSS, and may contribute to plaque progression. 140 In another similar study, plaques at the coronary bifurcation were found to induce low WSS in coronary side branches. 141 Lee et al 56 studied the flow around a plaque grown in a human carotid bifurcation.…”
Section: Plaque Developmentmentioning
confidence: 88%
See 1 more Smart Citation
“…These low-flow regions are associated with low WSS, and may contribute to plaque progression. 140 In another similar study, plaques at the coronary bifurcation were found to induce low WSS in coronary side branches. 141 Lee et al 56 studied the flow around a plaque grown in a human carotid bifurcation.…”
Section: Plaque Developmentmentioning
confidence: 88%
“…Particular attention has been paid to develop techniques that permit the measurement of WSS. 138,139 From the numerical point of view, Chaichana et al 140 performed a computational fluid-dynamics analysis involving model plaque in left coronary arteries to investigate the effect of plaque on the hemodynamics of flow. The presence of plaque was found to alter the pressure gradient, with higher gradients in the stenotic regions that may contribute to plaque rupture.…”
Section: Plaque Developmentmentioning
confidence: 99%
“…4) [2]. The exports were set as free flow boundary (Out-1 to 11), and the flow allocation was determined by diameter of each export depending on Murray law [3].…”
Section: Methodsmentioning
confidence: 99%
“…The graph of coronary arteries flow changes during cardiac cycle was reported by Chaichana et al [2]: time as abscissa (s) and quantity of flow as ordinate (mL/min). Flow of the entry of the left coronary artery (inlet) at different moment could be acquired.…”
Section: Methodsmentioning
confidence: 99%
“…Blood is usually a non-Newtonian fluid flowing through the artery. However, blood behaves as Newtonian fluid at high strain rate [28][29][30][31][32][33][34][35][36] and the density of blood is assumed 1050 kg/m 3 . The cell zone inside the artery is selected as blood and a steady state blood flow is assumed in the analysis.…”
Section: Computational Analysismentioning
confidence: 99%